2020
DOI: 10.3390/cells9092030
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Pigments Changes of Three Phenotypes of Picocyanobacteria Synechococcus sp. under Different Light and Temperature Conditions

Abstract: It is estimated that the genus Synechococcus is responsible for about 17% of net primary production in the Global Ocean. Blooms of these organisms are observed in tropical, subtropical and even temperate zones, and they have been recorded recently even beyond the polar circle. The long-term scenarios forecast a growing expansion of Synechococcus sp. and its area of dominance. This is, among others, due to their high physiological plasticity in relation to changing environmental conditions. Three phenotypes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 81 publications
(123 reference statements)
0
12
0
Order By: Relevance
“…In such a variable ecosystem as the Baltic Sea region, autotrophic organisms should show the ability to adapt quickly, which is crucial for their survival and the possibility of settling in new areas. The future climate changes leading to global warming may favor the development of picocyanobacterial—the smallest cell-size cyanobacteria (0.2–2 µm) [ 31 ]—which under high temperatures achieve the maximum abundance [ 32 , 33 ]. Our research, conducted between 2018 and 2020 in the southern Baltic Sea region, showed that the increasing intensity of light and temperature had a positive effect on the cell concentration of the studied cyanobacterium Nostoc sp., and for diatoms Nitzschia sp., Amphora sp., and Halamphora sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a variable ecosystem as the Baltic Sea region, autotrophic organisms should show the ability to adapt quickly, which is crucial for their survival and the possibility of settling in new areas. The future climate changes leading to global warming may favor the development of picocyanobacterial—the smallest cell-size cyanobacteria (0.2–2 µm) [ 31 ]—which under high temperatures achieve the maximum abundance [ 32 , 33 ]. Our research, conducted between 2018 and 2020 in the southern Baltic Sea region, showed that the increasing intensity of light and temperature had a positive effect on the cell concentration of the studied cyanobacterium Nostoc sp., and for diatoms Nitzschia sp., Amphora sp., and Halamphora sp.…”
Section: Resultsmentioning
confidence: 99%
“…For many cyanobacteria and microalgae, the high light intensity is an unfavorable environmental factor [ 44 ], which organisms can respond to by, for example, changing the concentration of pigments in cells [ 23 , 32 , 45 ]. Generally, the factorial experiments performed in this study showed a negative effect of the increasing irradiance on the content of the cell-specific pigment for the analyzed airborne cyanobacteria and microalgae, obtaining the highest contents at 10 μmol photons m −2 s −1 and the lowest for 190 μmol photons m −2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to different dominating species who have differential pigments compositions, because the pigments content, type, and arrangement inside the thylakoid membrane usually determine the size of the light-harvesting complex of PS II among phytoplankton groups (Suggett et al, 2009;Hughes et al, 2018b). Major pigments of Synechococcus to constitute the lightharvesting complexes are phycobilisomes (Sliwińska-Wilczewska et al, 2020), while that of Prochlorococcus are divinyl derivatives Chla/b (Ralf and Repeta, 1992); such a pigment difference may vary their light-harvesting abilities, thus leading to the differential photosynthetic responses to the acutely increased temperature between the surface and DCM layers. Larger σ PSII prevailed in the southern part of the surveyed areas where phytoplankton may have adaptively improved its light-harvesting abilities to sustain growth (Zhu et al, 2017;Sherman et al, 2020), because of the low nutrient status therein (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, PE-rich picocyanobacteria are often found in clear, oligotrophic waters where green and blue-green light is available, while PC-rich phenotypes are found in more turbid, eutrophic waters dominated by red underwater light [ 52 , 53 , 54 ] ( Figure 4 ). The presence of light-absorbing pigments at different wavelengths extends the occupancy of ecological niches with different light characteristics in the water column (e.g.,) [ 52 , 54 , 55 , 56 ]. Thus, the PBS, with its antenna pigments capable of using different wavelengths, is an advantage for Synechococcus , providing a functional basis for their adaptation to different underwater radiation conditions.…”
Section: The Genus Synechococcusmentioning
confidence: 99%